An economic and environmental assessment of guayule resin co-products for a US natural rubber industry - Silagy, Brooke, author; Reardon, Kenneth, advisor; Quinn, Jason C., advisor; Kipper, Matthew, committee member; Bradley, Thomas, committee member (Colorado State University. Libraries, 2023)
Guayule (Parthenium argentatum) is a natural rubber producing desert shrub that has the potential to be grown in semi-arid areas with limited water resources. Numerous studies have examined the costs and environmental impacts associated with guayule rubber production. These studies identified the need for additional value from the rubber co-products, specifically the resin, for sustainable and commercial viability of the biorefinery concept. This study developed process models for resin-based essential oils, insect repellant, and adhesive co-products that are integrated with sustainability assessments to understand the commercial viability. A techno-economic analysis and cradle-to-gate life cycle assessment (LCA) of these three different co-product pathways assumed a facility processing 66 tonnes/day of resin (derived from the processing of 1428 tonnes per day of guayule biomass) and included resin separation through co-product formation. The evaluation outcomes were integrated into an established guayule rubber production model to assess the economic potential and environmental impact of the proposed guayule resin conversion concepts. The minimum selling price for rubber varied by co-product: $3.54 per kg for essential oil, $3.40 per kg for insect repellent, and $1.69 per kg for resin blend adhesive. The resin blend adhesive co-product pathway had the lowest greenhouse gas emissions. These findings show a pathway that supports the development of a biorefining concept based on resin-based adhesives that can catalyze a US based natural rubber industry.
Keywords: distillation; life cycle assessment; techno-economic analysis; guayule; aspen plus; resin